2002
DOI: 10.1021/bi0263964
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Arginine Is Critical for the Functional Folding of Inhibitor of Apoptosis (IAP) BIR Domains

Abstract: The inhibitor of apoptosis (IAP) proteins are found in all animals and regulate apoptosis (programmed cell death) by binding and inhibiting caspase proteases. This inhibition is overcome by several apoptosis stimulators, including Drosophila Hid and mammalian Smac/DIABLO, which bind to 65-residue baculovirus IAP repeat (BIR) domains found in one to three copies in all IAPs. Virtually all BIRs contain three Cys and a His that bind zinc, a Gly in a tight turn, and an Arg. The functional and structural role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…4). Similar interactions are recognized as crucial for the structural stabilization of caspase BIR domain (28) and neutrophil collagenase (29). Moreover, (Phe-177) is the only residue of 682 modeled amino acid residues in a disallowed region of the Ramachandran plot in all mutant crystal structures as well as in precursor and mature CA (see Fig.…”
Section: Carboxyl Proteolytic Autocleavagementioning
confidence: 71%
“…4). Similar interactions are recognized as crucial for the structural stabilization of caspase BIR domain (28) and neutrophil collagenase (29). Moreover, (Phe-177) is the only residue of 682 modeled amino acid residues in a disallowed region of the Ramachandran plot in all mutant crystal structures as well as in precursor and mature CA (see Fig.…”
Section: Carboxyl Proteolytic Autocleavagementioning
confidence: 71%
“…This region encompasses the C-terminal two-thirds of the BIR1 domain, which contains the conserved CX 2 CX 16 HX 6À8 C motif capable of coordinating a zinc ion. This conserved 'zinc-finger' structure underlies the surface groove where caspases bind to IAP BIR domains (Luque et al, 2002). It is tempting to speculate that this zinc finger may mediate oligomerization by interacting in some way with the caspase-like domain of the MALT1 moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Smac is capable of binding to the BIR domains of XIAP, c-IAP1, c-IAP2, Melanoma IAP (ML-IAP), and OpIAP from the baculovirus O. pseudotsugata [10,21,47,48], and an interaction with survivin was originally suggested but could not be proven unambiguously [11]. The single BIR domain of survivin bears a close structural homology to BIR2 of XIAP [49], including the critical arginine residue required for functional folding [50]. Recently, it was suggested that Smac and survivin can bind to each other, an interaction essential for inhibition of Taxolmediated apoptosis in HeLa cells [51].…”
Section: Discussionmentioning
confidence: 99%